The bed nucleus of stria terminalis and the amygdala as targets of antenatal glucocorticoids: implications for fear and anxiety responses - Oliveira, Mário (2012)
Rationale: Several human and experimental studies have shown that early life adverse events can shape physical and mental health in adulthood. Stress or elevated levels of glucocorticoids (GCs) during critical periods of development seem to contribute for the appearance of neurospyschiatric conditions such as anxiety and depression, albeit the underlying mechanisms remain to be fully elucidated. Objectives: The aim of the present study was to determine the long-term effect of prenatal erxposure to dexamethasone- DEX (synthetic GC widely used in clinics) in fear and anxious behavior and identify the neurochemical, morphological and molecular correlates. Results: Prenatal exposure to DEX triggers a hyperanxious phenotype and altered fear behavior in adulthood. These behavioral traits were correlated with increased volume of the bed nucleus of the stria terminalis (BNST), particularly the anteromedial subivision which presented increased dendritic length; in parallel, we found an increased expression of synapsin and NCAM in the BNST of these animals. Remarkably, DEX effects were opposite in the amygdala, as this region presented reduced volume due to significant dendritic atrophy. Albeit no differences were found in dopamine and its metabolite levels in the BNST, this neurotransmitter was substantially reduced in the amygdala, which also presented an up-regulation of dopamine receptor 2. Conclusions: Altogether our results show that in utero DEX exposure can modulate anxiety and fear behavior in parallel with significant morphological, neurochemical and molecular changes; importantly, GCs seem to differentially affect distinct brain regions involved in this type of behaviors.